2004
DOI: 10.1007/s00277-004-0927-y
|View full text |Cite
|
Sign up to set email alerts
|

Combination of liposomal daunorubicin (DaunoXome), fludarabine, and cytarabine (FLAD) in patients with poor-risk acute leukemia

Abstract: Sixty-two patients with high-risk acute leukemia were treated with the FLAD regimen [3 days of treatment with fludarabine 30 mg/m(2), cytarabine (AraC) 2 g/m(2), and liposomal daunorubicin 80 mg/m(2)]. The acute myeloid leukemia (AML) patients were either refractory to standard induction regimens (8), were in first or second relapse (13), or received therapy as first-line treatment [21 patients, 16 were above 60 years of age and 5 had post-myelodysplastic syndrome (MDS) AML]. The acute lymphoblastic leukemia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…Similar results have been recently published by Clavio et al [29] using a salvage treatment with the same drugs as in this study but without continuous infusion in a variety of patients with poor-risk acute leukemias (ALL, AML resistant or relapsed, de novo AML in elderly people).…”
Section: Discussionsupporting
confidence: 91%
“…Similar results have been recently published by Clavio et al [29] using a salvage treatment with the same drugs as in this study but without continuous infusion in a variety of patients with poor-risk acute leukemias (ALL, AML resistant or relapsed, de novo AML in elderly people).…”
Section: Discussionsupporting
confidence: 91%
“…15,16 Recent studies have utilized a combination of liposomal daunorubicin (DNX), fludarabine, and cytarabine in patients with poor risk acute leukemia and proved to be effective in inducing high complete response (CR) rates without the occurrence of significant toxicity. [16][17][18] Similarly, Melillo et al 19 reported the experience of the combination of nonpegylated liposomal doxorubicin (Myocet) with FLAG regimen in a cohort of adult poor prognosis AML patients. Myocet has a longer half life than standard doxorubicin, significantly less cardiotoxicity, and comparable antitumor efficacy.…”
mentioning
confidence: 99%
“…This form of fludarabine has the ability to prevent the activity of enzymes involved in DNA synthesis and DNA repair. Inhibition of DNA polymerase alpha, DNA primase, ligase, and reductase induces DNA damage and arrest the cell cycle (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%